Processor load balancing for parallel branch and bound algorithms - Baravykaitė, Milda (Lietuvos matematikos rinkinys, 2005)
In this atricle the development of parallel branch and bound algorithm template is presented. Attention is ocused on the dynamic load balancing module of the template. The structure of dynamic load balancing is disscussed and some results of calculation experiments are presented.